The Effect of the STAD Cooperative Learning Model on Student Learning Outcomes in Reaction Rate Material - Siti Zharifah Najla Mehar; Evi Sapinatul Bahriah (Jambura Journal of Educational Chemistry, 2025)
The purpose of this research is to examine how student learning outcomes in reaction rate material are impacted by the Student Teams Achievement Division (STAD) cooperative learning model. The study used a quasi-experimental method with a posttest only nonequivalent control group design. Purposively, the sample was chosen, with 30 students in each of the two classes, XI SAINKES 4 as the experimental class and XI SAINKES 1 as the control class. Student Worksheets (LKPD) and twenty multiple choice post-test questions were among the tools utilized. Data were collected through written tests and documentation, then analyzed using normality tests, homogeneity tests, and hypothesis tests with independent sample t-tests using IBM SPSS Statistics 26. According to the findings, the experimental class’s average post-test score was 74, whereas the control class’s was 55,67. The hypothesis test showed a Sig. (2-tailed) value of 0,000 (p < 0,05), so the alternative hypothesis was accepted. Thus, student learning outcomes in reaction rate material were significantly impacted by the use of the STAD cooperative learning model.